Study on the potential mechanism, therapeutic drugs and prescriptions of insomnia based on bioinformatics and molecular docking. (October 2022) - Huang, Xulong; Jiang, Huajuan; Pei, Jin; Wu, Qinghua; Wu, Weihua; Ren, Chaoxiang; Zhou, Lanyu; zhou, Yongfeng; Xian, Bin; Chen, Chao; Yan, Yuhang; Lu, Lijie; et al.
Abstract: Insomnia is a very common disease worldwide. It seriously affects the quality of human life and even endangers health. Traditional Chinese medicine (TCM) has unique advantages in the intervention and treatment of insomnia. However, its underlying mechanism has yet to be elucidated. This study was performed to explore the potential biomarkers and mechanisms of insomnia, and treatment TCM and classical prescriptions. The gene microarray data of insomnia is downloaded and preprocessed. Differentially expressed genes (DEGs) and GO and KEGG enrichment analyses were performed. The protein-protein interaction network (PPI) was constructed. Small molecule drugs for curing insomnia were identified using cMap and CTD databases. We searched the TCM corresponding to small molecule drugs and the classic prescriptions corresponding to TCM by the TCMSP database. We constructed a network of "ingredient-TCM-classic prescriptions". The molecular docking was performed to validate the screening results. We obtained a total of 124 DEGs, including 78 up-regulated genes, 46 down-regulated genes, 10 Hub genes and 3 key modules. A total of 125 significant GO entries and 15 significant KEGG were enriched (P < 0.05). The main biological processes involve neuronal apoptosis, autophagy, cell growth and apoptosis, etc. These signaling pathways may be involved in molecular regulatory mechanisms of insomnia, such as autophagy regulation, Alzheimer's disease, pathways to neurodegenerative diseases and neurotrophic factor signaling pathways. We identified 10 traditional Chinese medicines and 2 classical prescriptions of potential value. In addition, the molecular docking results indicated that small molecule ligands were nicely bound to the Hub gene, and the binding affinity ranged from −7.6 to −9.7 kcal/mol. This study provides a foundation for the clinical treatment of insomnia, explains the molecular mechanisms, and efficiently develops TCM and classical prescriptions. Graphical abstract: Image 1 Highlights: Insomnia of potential biomarkers and treatment medicines were identified by genechip expression data and network pharmacology. The molecular mechanism of insomnia was elucidated by bioinformatics analysis and molecular docking. The study provides an effective way for the insomnia of TCM.